Calcium-magnesium-silicon system microcrystalline glass low-temperature co-fired ceramic material and preparation method thereof
Patent Information
- Application Number
- CN202611173816.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-13
AI Technical Summary
然而,现有CBS系低温共烧陶瓷在高频段下的介电性能仍有待提高,尤其是介电损耗在高频条件下呈上升趋势,导致信号衰减加剧,影响通信质量
[0015]发明提供了一种钙镁硅系微晶玻璃低温共烧陶瓷材料的制备方法,包括以下步骤:将钙镁硅玻璃粉(CMS玻璃粉)和粘结剂混合后依次进行陈腐、造粒和压制成型,得到素坯;所述钙镁硅玻璃粉中各组分的摩尔百分比为:MgO 20~25%,CaO 25~40 %,SiO240~50 %;将所述素坯进行烧结,得到所述钙镁硅系微晶玻璃低温共烧陶瓷材料。本发明提供的钙镁硅系微晶玻璃低温共烧陶瓷材料具有优异的介电性能、较低的介电损耗以及良好的烧结特性,并且结构致密、可靠性好;与传统硼硅酸盐体系相比,本发明采用无硼体系原料、环境友好、原料无腐蚀性,不易对人体产生危害,并且不存在硼元素挥发的问题;同时,本发明制备的低温共烧陶瓷材料还具有优异的力学性能,能够在保持低介电损耗和热稳定性的基础上弥补传统硼硅酸盐体系力学强度不足的问题;本发明提供的制备方法工艺简单、生产周期短、产量高、环境友好。
Smart Images

Figure CN122897673A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of microwave dielectric materials technology, and in particular to a calcium-magnesium-silicon microcrystalline glass low-temperature co-fired ceramic material and its preparation method. Background Technology
[0002] With the increasing demand for high-frequency technologies in the electronics industry, low-temperature co-fired ceramics (LTCC) have become a key material for meeting the high signal transmission rate and high performance requirements of integrated circuits due to their superior dielectric properties and the advantages of the low-temperature co-firing process. In the field of high-frequency microwave communication, the dielectric constant of the dielectric material is negatively correlated with the signal transmission speed—that is, the smaller the dielectric constant, the lower the signal propagation delay in the medium, and the faster the transmission rate. Therefore, LTCC substrates need to adopt low-dielectric-constant material systems to reduce dielectric loss and signal attenuation, thereby achieving high-speed, low-latency signal transmission and effectively supporting the performance optimization of high-frequency communication systems. Given that existing LTCC materials are difficult to adapt to the stringent requirements of high-frequency communication, the development of novel high-performance microcrystalline glass systems has significant practical implications.
[0003] Currently, the most widely used LTCC (Low Temperature Co-fired Ceramic) microcrystalline materials are borosilicate systems, with the CaO-B₂O₃-SiO₂ (CBS) system being one of the most prevalent. However, the dielectric properties of existing CBS-based low-temperature co-fired ceramics at high frequencies still need improvement, especially as dielectric loss increases under high-frequency conditions, leading to increased signal attenuation and affecting communication quality. Furthermore, borosilicate systems also suffer from boron volatilization, which may affect the long-term reliability of the materials. Summary of the Invention
[0004] In view of this, the present invention provides a calcium-magnesium-silicon microcrystalline glass-based low-temperature co-fired ceramic material and its preparation method. The calcium-magnesium-silicon microcrystalline glass-based low-temperature co-fired ceramic material provided by the present invention has excellent dielectric properties, low loss, and uses boron-free raw materials, thus eliminating the problem of boron volatilization.
[0005] To achieve the above-mentioned objectives, the present invention provides the following technical solution: A method for preparing a calcium-magnesium-silicon microcrystalline glass-based low-temperature co-fired ceramic material includes the following steps: After mixing calcium magnesium silicate glass powder and binder, the mixture is successively aged, granulated, and pressed to obtain a green body; the molar percentage of each component in the calcium magnesium silicate glass powder is: MgO 20~25%, CaO 25~40%, SiO 240~50%; The green blank is sintered to obtain the calcium-magnesium-silicon microcrystalline glass low-temperature co-fired ceramic material.
[0006] Preferably, the method for preparing the calcium magnesium silicon glass powder includes: mixing MgO, CaCO3 and SiO2 and heating to melt them to obtain molten glass liquid; quenching the molten glass liquid with water to obtain a glass body; and ball milling the glass body to obtain calcium magnesium silicon glass powder; wherein the amount of CaCO3 is calculated as CaO.
[0007] Preferably, the heating and melting temperature is 1450~1550℃, and the holding time is 1~3h.
[0008] Preferably, the ball milling conditions include: the ball milling medium is ethanol, the grinding balls are zirconia balls, the ball milling speed is 350~400 rpm, and the ball milling time is 5~7 h.
[0009] Preferably, the binder is a polyvinyl alcohol solution with a mass concentration of 3-5%; the mass ratio of the polyvinyl alcohol solution to the calcium magnesium silicate glass powder is 1:(35-45).
[0010] Preferably, the pressing pressure is 70~100MPa.
[0011] Preferably, the sintering temperature is 800~900℃ and the holding time is 30~60min.
[0012] Preferably, the heating rate to the sintering temperature is 4~6℃ / min.
[0013] The present invention also provides a calcium-magnesium-silicon microcrystalline glass low-temperature co-fired ceramic material prepared by the preparation method described above.
[0014] Preferably, the calcium-magnesium-silicon microcrystalline glass-ceramic material has a dielectric constant of 7.22-8.98 and a dielectric loss of (1.24-4.79)×10⁻⁶ at 11-13 GHz. -3 .
[0015] The invention provides a method for preparing a calcium-magnesium-silicon microcrystalline glass-low temperature co-fired ceramic material, comprising the following steps: mixing calcium-magnesium-silicon glass powder (CMS glass powder) and a binder, and then sequentially aging, granulating, and pressing to obtain a green body; the molar percentage of each component in the calcium-magnesium-silicon glass powder is: MgO 20~25%, CaO 25~40%, SiO2 40~50%; sintering the green body to obtain the calcium-magnesium-silicon microcrystalline glass-low temperature co-fired ceramic material. The calcium-magnesium-silicon microcrystalline glass-based low-temperature co-fired ceramic material provided by this invention possesses excellent dielectric properties, low dielectric loss, and good sintering characteristics, as well as a dense structure and high reliability. Compared with traditional borosilicate systems, this invention uses boron-free raw materials, is environmentally friendly, uses non-corrosive raw materials, is unlikely to cause harm to the human body, and does not have the problem of boron volatilization. At the same time, the low-temperature co-fired ceramic material prepared by this invention also has excellent mechanical properties, which can compensate for the insufficient mechanical strength of traditional borosilicate systems while maintaining low dielectric loss and thermal stability. The preparation method provided by this invention is simple, has a short production cycle, high yield, and is environmentally friendly.
[0016] The results of the examples show that the calcium-magnesium-silicon microcrystalline glass-based low-temperature co-fired ceramic material prepared in this invention has a dielectric constant of 7.22~8.98 and a dielectric loss of (1.24~4.79)×10⁻⁶ under test conditions of 11~13 GHz. -3 It can meet the application requirements of low-temperature co-fired ceramic materials in the field of high-frequency communication. Attached Figure Description
[0017] Figure 1 The XRD patterns of the CMS glass powders prepared in Examples 1-6 are shown below. Figure 2 The DSC curves of the CMS glass powders prepared in Examples 1-6 are shown. Figure 3 The FT-IR spectra of the CMS glass powders prepared in Examples 1-6 are shown below. Figure 4 The images show the XRD patterns of the CMS microcrystalline glass low-temperature co-fired ceramic materials prepared in Examples 1-6. Detailed Implementation
[0018] This invention provides a method for preparing a calcium-magnesium-silicon microcrystalline glass-based low-temperature co-fired ceramic material, comprising the following steps: After mixing calcium magnesium silicate glass powder and binder, the mixture is successively aged, granulated, and pressed to obtain a green body; the molar percentage of each component in the calcium magnesium silicate glass powder is: MgO 20~25%, CaO 25~40%, SiO 240~50%; The green blank is sintered to obtain the calcium-magnesium-silicon microcrystalline glass low-temperature co-fired ceramic material.
[0019] This invention involves mixing calcium magnesium silicate glass powder and a binder, followed by sequential aging, granulation, and pressing to obtain a green body. In this invention, the molar percentages of each component in the calcium magnesium silicate glass powder are: MgO 20-25%, CaO 25-40%, and SiO2 40-50%. In specific embodiments of this invention, the molar percentage of MgO in the calcium magnesium silicate glass powder can be 20%, 21.043%, 22.58%, 23.53%, 24.32%, or 25%; the molar percentage of CaO can be 25%, 27.03%, 29.41%, 32.26%, 35.71%, or 40%; and the molar percentage of SiO2 can be 40%, 42.86%, 45.16%, 47.06%, 48.65%, or 50%.
[0020] In this invention, the molar ratio of SiO2 to CaO (denoted as Si / Ca) in the calcium magnesium silicon glass powder is preferably 1 to 2, specifically 1, 1.2, 1.4, 1.6, 1.8 or 2; the molar ratio of MgO to SiO2 (denoted as Mg / Si) is preferably 0.5.
[0021] In this invention, the preferred method for preparing the calcium magnesium silicate glass powder includes: mixing MgO, CaCO3, and SiO2 and heating to melt them to obtain molten glass; quenching the molten glass in water to obtain a glass body; ball milling the glass body to obtain calcium magnesium silicate glass powder; the amount of CaCO3 used is calculated as CaO; the mixing of MgO, CaCO3, and SiO2 is preferably carried out in a three-dimensional mixer, and the mixing time is preferably 1 h; the heating and melting temperature is preferably 1450~1550℃, specifically 1500℃, and the holding time is preferably 1~3 h, specifically 2 h, and the heating and melting is carried out in a resistance furnace; the water quenching specifically involves pouring the molten glass into deionized water for rapid quenching; the ball milling conditions preferably include: the ball milling medium is ethanol, the grinding balls are zirconia balls, the ball milling speed is 350~400 rpm, and the ball milling time is 5~7 h, specifically 6 h. The process after ball milling preferably includes sieving and drying the resulting powder, wherein the mesh size of the sieve used for sieving is preferably 500 mesh, and the drying temperature is preferably 80°C.
[0022] In this invention, the binder is preferably a polyvinyl alcohol solution, and the mass concentration of the polyvinyl alcohol solution is preferably 3-5%, specifically 4%; the mass ratio of the polyvinyl alcohol solution to the calcium magnesium silicate glass powder is preferably 1:(35-45), specifically 1:40.
[0023] In this invention, the aging time is preferably 18-24 hours; this invention has no special requirements for sieving and granulation, and can use methods well known to those skilled in the art; the pressing pressure is preferably 70-100 MPa, and the pressing is preferably carried out using a unidirectional tablet press; in a specific embodiment of this invention, the preform is a Φ10 mm × 5 mm circular preform.
[0024] After obtaining the green blank, the present invention sintersulates the green blank to obtain the calcium-magnesium-silicon microcrystalline glass-low temperature co-fired ceramic material. In the present invention, the sintering temperature is preferably 800~900℃, specifically 850℃, and the holding time is preferably 30~60min; the heating rate to the sintering temperature is preferably 4~6℃ / min, specifically 5℃ / min; after sintering, the material is cooled in the furnace to obtain the calcium-magnesium-silicon microcrystalline glass-low temperature co-fired ceramic material. By controlling the above conditions, the present invention can achieve dense sintering of the material and precipitate Ca2MgSi2O7 and CaMgSi2O6 crystal phases.
[0025] This invention also provides a calcium-magnesium-silicon microcrystalline glass-low temperature co-fired ceramic material prepared by the preparation method described above. In this invention, the calcium-magnesium-silicon microcrystalline glass-low temperature co-fired ceramic material has a Ca2MgSi2O7 crystalline phase, or simultaneously has both Ca2MgSi2O7 and CaMgSi2O6 crystalline phases. In a specific embodiment of this invention, when Si / Ca is greater than or equal to 1 and less than 1.6, the calcium-magnesium-silicon microcrystalline glass-low temperature co-fired ceramic material is a pure Ca2MgSi2O7 crystalline phase; when Si / Ca is greater than or equal to 1.6 and less than or equal to 2, both Ca2MgSi2O7 and CaMgSi2O6 crystalline phases coexist in the calcium-magnesium-silicon microcrystalline glass-low temperature co-fired ceramic material.
[0026] In this invention, the calcium-magnesium-silicon microcrystalline glass-based low-temperature co-fired ceramic material has a dielectric constant of 7.22~8.98 and a dielectric loss of (1.24~4.79)×10⁻¹⁰ at 11~13 GHz (specifically 12.6~13.5 GHz). -3 .
[0027] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0028] Example 1 Preparation of low-temperature co-fired ceramic materials of 40.00 mol% CaO-20.00 mol% MgO-40.00 mol% SiO2 microcrystalline glass: Step 1: Using MgO, CaCO3, and SiO2 as raw materials (purity ≥ 99%), weigh them according to the ratio of MgO, CaO, and SiO2 in the target product and mix them in a three-dimensional mixer for 1 hour. After thoroughly mixing the raw materials, heat them to 1500 ℃ in a resistance furnace and hold for 2 hours to obtain molten glass. Then pour the molten glass into deionized water and rapidly quench it to obtain the glass body.
[0029] Step 2: The glass body was placed in a planetary ball mill for ball milling. The milling media was ethanol, and the grinding balls were zirconia balls. The ball mill speed was 350 rpm, and the milling time was 6 hours. The ball-milled glass powder was then passed through a 500-mesh sieve and dried in an 80 ℃ oven to obtain CMS glass powder.
[0030] Step 3: Add a 4 wt% polyvinyl alcohol solution (polyvinyl alcohol solution to CMS glass powder mass ratio of 1:40) to the CMS glass powder, and then perform aging, sieving, and granulation to obtain a mixed powder. Press the mixed powder on a unidirectional tablet press at a pressure of 100 MPa to obtain a Φ10 mm × 5 mm round blank.
[0031] Step 4: Place the green blank in a muffle furnace and heat it to 850 ℃ at a heating rate of 5 ℃ / min. Hold the temperature for 30 min and then cool it with the furnace to obtain a microcrystalline glass with a composition of 40.00 mol%CaO-20.00 mol%MgO-40.00 mol%SiO2. In this example, Mg / Si=0.5 and Si / Ca=1.0.
[0032] Example 2 Preparation of low-temperature co-fired ceramic materials of 35.71 mol% CaO-21.43 mol% MgO-42.86 mol% SiO2 microcrystalline glass: Step 1: Using MgO, CaCO3, and SiO2 as raw materials (purity ≥ 99%), weigh them according to the ratio of MgO, CaO, and SiO2 in the target product and mix them in a three-dimensional mixer for 1 hour. After thoroughly mixing the raw materials, heat them to 1500 ℃ in a resistance furnace and hold for 2 hours to obtain molten glass. Then pour the molten glass into deionized water and rapidly quench it to obtain the glass body.
[0033] Step 2: The glass body was placed in a planetary ball mill for ball milling. The milling media was ethanol, and the grinding balls were zirconia balls. The ball mill speed was 350 rpm, and the milling time was 6 hours. The ball-milled glass powder was then passed through a 500-mesh sieve and dried in an 80 ℃ oven to obtain CMS glass powder.
[0034] Step 3: Add a 4 wt% polyvinyl alcohol solution (polyvinyl alcohol solution to CMS glass powder mass ratio of 1:40) to the CMS glass powder, and then perform aging, sieving, and granulation to obtain a mixed powder of glass powder and polyvinyl alcohol solution. Press the mixed powder on a unidirectional tablet press at a pressure of 100 MPa to obtain a Φ10 mm × 5 mm round blank.
[0035] Step 4: Place the green blank in a muffle furnace and heat it to 850 ℃ at a heating rate of 5 ℃ / min. Hold the temperature for 30 min and then cool it with the furnace to obtain a microcrystalline glass with a composition of 35.71 mol%CaO-21.43 mol%MgO-42.86 mol%SiO2. In this example, Mg / Si=0.5 and Si / Ca=1.2.
[0036] Example 3 Preparation of low-temperature co-fired ceramic materials of 32.26 mol% CaO-22.58 mol% MgO-45.16 mol% SiO2 microcrystalline glass: Step 1: Using MgO, CaCO3, and SiO2 as raw materials (purity ≥ 99%), weigh them according to the ratio of MgO, CaO, and SiO2 in the target product and mix them in a three-dimensional mixer for 1 hour. After thoroughly mixing the raw materials, heat them to 1500 ℃ in a resistance furnace and hold for 2 hours to obtain molten glass. Then pour the molten glass into deionized water and rapidly quench it to obtain the glass body.
[0037] Step 2: The glass body was placed in a planetary ball mill for ball milling. The milling media was ethanol, and the grinding balls were zirconia balls. The ball mill speed was 350 rpm, and the milling time was 6 hours. The ball-milled glass was then passed through a 500-mesh sieve and dried in an 80 ℃ oven to obtain CMS glass powder.
[0038] Step 3: Add a 4 wt% polyvinyl alcohol solution (polyvinyl alcohol solution to CMS glass powder mass ratio of 1:40) to the CMS glass powder, and then perform aging, sieving, and granulation to obtain a mixed powder of glass powder and polyvinyl alcohol solution. Press the mixed powder on a unidirectional tablet press at a pressure of 100 MPa to obtain a Φ10 mm × 5 mm round blank.
[0039] Step 4: Place the green blank in a muffle furnace and heat it to 850 ℃ at a heating rate of 5 ℃ / min. Hold the temperature for 30 min and then cool it with the furnace to obtain a microcrystalline glass with a composition of 32.26 mol%CaO-22.58 mol%MgO-45.16 mol%SiO2. In this example, Mg / Si=0.5 and Si / Ca=1.4.
[0040] Example 4 Preparation of low-temperature co-fired ceramic materials of 29.41 mol% CaO-23.53 mol% MgO-47.06 mol% SiO2 microcrystalline glass: Step 1: Using MgO, CaCO3, and SiO2 as raw materials (purity ≥ 99%), weigh them according to the ratio of MgO, CaO, and SiO2 in the target product and mix them in a three-dimensional mixer for 1 hour. After thoroughly mixing the raw materials, heat them to 1500 ℃ in a resistance furnace and hold for 2 hours to obtain molten glass. Then pour the molten glass into deionized water and rapidly quench it to obtain the glass body.
[0041] Step 2: The glass body was placed in a planetary ball mill for ball milling. The milling media was ethanol, and the grinding balls were zirconia balls. The ball mill speed was 350 rpm, and the milling time was 6 hours. The ball-milled glass was then passed through a 500-mesh sieve and dried in an 80 ℃ oven to obtain CMS glass powder.
[0042] Step 3: Add a 4 wt% polyvinyl alcohol solution (polyvinyl alcohol solution to CMS glass powder mass ratio of 1:40) to the CMS glass powder, and then perform aging, sieving, and granulation to obtain a mixed powder of glass powder and polyvinyl alcohol solution. Press the mixed powder on a unidirectional tablet press at a pressure of 100 MPa to obtain a Φ10 mm × 5 mm round blank.
[0043] Step 4: Place the green blank in a muffle furnace and heat it to 850 ℃ at a heating rate of 5 ℃ / min. Hold the temperature for 30 min and then cool it with the furnace to obtain a microcrystalline glass with a composition of 29.41 mol%CaO-23.53 mol%MgO-47.06 mol%SiO2. In this example, Mg / Si=0.5 and Si / Ca=1.6.
[0044] Example 5 Preparation of low-temperature co-fired ceramic materials of 27.03 mol% CaO-24.32 mol% MgO-48.65 mol% SiO2 microcrystalline glass: Step 1: Using MgO, CaCO3, and SiO2 as raw materials (purity ≥ 99%), weigh them according to the ratio of MgO, CaO, and SiO2 in the target product and mix them in a three-dimensional mixer for 1 hour. After thoroughly mixing the raw materials, heat them to 1500 ℃ in a resistance furnace and hold for 2 hours to obtain molten glass. Then pour the molten glass into deionized water and rapidly quench it to obtain the glass body.
[0045] Step 2: The glass body was placed in a planetary ball mill for ball milling. The milling media was ethanol, and the grinding balls were zirconia balls. The ball mill speed was 350 rpm, and the milling time was 6 hours. The ball-milled glass was then passed through a 500-mesh sieve and dried in an 80 ℃ oven to obtain CMS glass powder.
[0046] Step 3: Add a 4 wt% polyvinyl alcohol solution (polyvinyl alcohol solution to CMS glass powder mass ratio of 1:40) to the CMS glass powder, and then perform aging, sieving, and granulation to obtain a mixed powder of glass powder and polyvinyl alcohol solution. Press the mixed powder on a unidirectional tablet press at a pressure of 100 MPa to obtain a Φ10 mm × 5 mm round blank.
[0047] Step 4: Place the green blank in a muffle furnace and heat it to 850 ℃ at a heating rate of 5 ℃ / min. Hold the temperature for 30 min and then cool it with the furnace to obtain a microcrystalline glass with a composition of 27.03 mol%CaO-24.32 mol%MgO-48.65 mol%SiO2. In this example, Mg / Si=0.5 and Si / Ca=1.8.
[0048] Example 6 Preparation of low-temperature co-fired ceramic materials of 25.00 mol% CaO-25.00 mol% MgO-50.00 mol% SiO2 microcrystalline glass: Step 1: Using MgO, CaCO3, and SiO2 as raw materials (purity ≥ 99%), weigh them according to the ratio of MgO, CaO, and SiO2 in the target product and mix them in a three-dimensional mixer for 1 hour. After thoroughly mixing the raw materials, heat them to 1500 ℃ in a resistance furnace and hold for 2 hours to obtain molten glass. Then pour the molten glass into deionized water and rapidly quench it to obtain the glass body.
[0049] Step 2: The glass body was placed in a planetary ball mill for ball milling. The milling media was ethanol, and the grinding balls were zirconia balls. The ball mill speed was 350 rpm, and the milling time was 6 hours. The ball-milled glass was then passed through a 500-mesh sieve and dried in an 80 ℃ oven to obtain CMS glass powder.
[0050] Step 3: Add a 4 wt% polyvinyl alcohol solution (polyvinyl alcohol solution to CMS glass powder mass ratio of 1:40) to the CMS glass powder, and then perform aging, sieving, and granulation to obtain a mixed powder of glass powder and polyvinyl alcohol solution. Press the mixed powder on a unidirectional tablet press at a pressure of 100 MPa to obtain a Φ10 mm × 5 mm round blank.
[0051] Step 4: Place the green blank in a muffle furnace and heat it to 850 ℃ at a heating rate of 5 ℃ / min. Hold the temperature for 30 min and then cool it with the furnace to obtain a microcrystalline glass with a composition of 25.00 mol%CaO-25.00 mol%MgO-50.00 mol%SiO2. In this example, Mg / Si=0.5 and Si / Ca=2.0.
[0052] Performance testing The dielectric constant and dielectric loss of the low-temperature co-fired ceramic materials prepared in Examples 1-6 were tested, and the test results are shown in Table 1.
[0053] Table 1 Dielectric performance test results
[0054] As can be seen from the data in Table 1, the CMS microcrystalline glass low-temperature co-fired ceramic material prepared by this invention has a small dielectric constant, low dielectric loss, and excellent dielectric properties.
[0055] Figure 1 The XRD patterns are of the CMS glass powders prepared in Examples 1-6. Figure 1 It can be seen that there are no obvious diffraction peaks in the XRD pattern, only a peak at around 30°, indicating that all CMS glass powders are completely amorphous and are all in an amorphous state.
[0056] Figure 2 The DSC curves are for the CMS glass powders prepared in Examples 1-6. Figure 2 It can be seen that at a heating rate of 5℃ / min, most glass samples exhibit a distinct glass transition temperature (T0). g ), crystallization start temperature (T) c ) and exothermic crystallization peak temperature (T p The exothermic crystallization peak temperature (T) of the glass sample p It is related to the formation of Ca2MgSi2O7 and CaMgSi2O6 crystal phases.
[0057] Figure 3 The FTIR spectra of the CMS glass powders prepared in Examples 1-6 are shown. Figure 3 It can be seen that all samples show a diameter of approximately 510 cm. -1 705 cm -1 850 cm -1 and 968 cm -1 The characteristic absorption bands in the vicinity indicate that the glass network structures under different Si / Ca ratios possess similar fundamental vibrational units. 510 cm⁻¹ -1The nearby absorption peaks can generally be attributed to Si-O-Si bending vibrations, and may also be related to low-wavenumber vibrations of the silicate network involving Ca-O / Mg-O. (Approximately 705 cm⁻¹) -1 The absorption band at this point can be attributed to the Si-O-Si symmetric stretching vibration or bridging oxygen-related bending vibration in the silicate structure, reflecting the connectivity between silicon-oxygen tetrahedra. (Approximately 850 cm⁻¹) -1 The absorption peaks nearby are generally associated with Si-O containing non-bridging oxygen. - This is related to stretching vibrations and may correspond to silicon-oxygen structural units with a lower degree of polymerization. 968 cm -1 The strong absorption peaks in the vicinity can be attributed to Si-O-Si or Si-O in the silicon-oxygen tetrahedron. - The stretching vibration. In the CaO-MgO-SiO2 glass system, Ca... 2+ and Mg 2+ As a network-modifying ion, it can break some Si-O-Si bridging oxygen bonds, generating non-bridging oxygen structures. Therefore, the absorption peak in this region is usually related to the Q in the silicate network. n The structural units and the content of non-bridging oxygen are closely related. As the Si / Ca ratio increases, the peak remains significant, indicating that the silicon-oxygen network structure always dominates in the sample.
[0058] Figure 4 The images show the XRD patterns of the CMS glass-ceramics prepared in Examples 1-6. Figure 4 It can be seen that after sintering at 850 °C for 30 min, when the Si / Ca ratio is low, the obtained CMS glass-ceramic precipitates pure Ca2MgSi2O7 crystalline phase, and the diffraction peak intensity of the Ca2MgSi2O7 crystalline phase increases with increasing Si / Ca ratio. When the Si / Ca ratio increases to 1.6, the CaMgSi2O6 phase begins to precipitate, while the Ca2MgSi2O7 crystalline phase decreases with increasing Si / Ca ratio. These results indicate that the selective precipitation and content control of Ca2MgSi2O7 and CaMgSi2O6 crystalline phases can be achieved by simply adjusting the Si / Ca ratio.
[0059] In summary, this invention successfully prepared CaO-MgO-SiO2-based microcrystalline glass-low-temperature co-fired ceramic materials with excellent dielectric properties through a combination of melt quenching and low-temperature sintering processes, which have promising application prospects in the field of high-frequency communication.
[0060] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a calcium-magnesium-silicon microcrystalline glass-based low-temperature co-fired ceramic material, characterized in that, Includes the following steps: After mixing calcium magnesium silicate glass powder and binder, the mixture is successively aged, granulated, and pressed to obtain a green blank; the molar percentages of each component in the calcium magnesium silicate glass powder are: MgO 20~25%, CaO 25~40%, SiO2 40~50%; The green blank is sintered to obtain the calcium-magnesium-silicon microcrystalline glass low-temperature co-fired ceramic material.
2. The preparation method according to claim 1, characterized in that, The preparation method of the calcium magnesium silicon glass powder includes: mixing MgO, CaCO3 and SiO2 and heating to melt them to obtain molten glass liquid; quenching the molten glass liquid with water to obtain a glass body; and ball milling the glass body to obtain calcium magnesium silicon glass powder; wherein the amount of CaCO3 used is calculated as CaO.
3. The preparation method according to claim 2, characterized in that, The heating and melting temperature is 1450~1550℃, and the holding time is 1~3h.
4. The preparation method according to claim 2, characterized in that, The conditions for ball milling include: the milling medium is ethanol, the milling balls are zirconia balls, the milling speed is 350~400 rpm, and the milling time is 5~7 h.
5. The preparation method according to claim 1, characterized in that, The binder is a polyvinyl alcohol solution with a mass concentration of 3-5%; the mass ratio of the polyvinyl alcohol solution to the calcium magnesium silicate glass powder is 1:(35-45).
6. The preparation method according to claim 1, characterized in that, The pressure for compression molding is 70~100MPa.
7. The preparation method according to claim 1, characterized in that, The sintering temperature is 800~900℃, and the holding time is 30~60min.
8. The preparation method according to claim 7, characterized in that, The heating rate to the sintering temperature is 4~6℃ / min.
9. The calcium-magnesium-silicon microcrystalline glass low-temperature co-fired ceramic material prepared by the preparation method according to any one of claims 1 to 8.
10. The calcium-magnesium-silicon microcrystalline glass-based low-temperature co-fired ceramic material according to claim 9, characterized in that, The calcium-magnesium-silicon microcrystalline glass-based low-temperature co-fired ceramic material has a dielectric constant of 7.22–8.98 and a dielectric loss of (1.24–4.79) × 10⁻⁶ at 11–13 GHz. -3 .